DATA SPECIFICATION PROGRAM, DATA SPECIFICATION METHOD, AND INFORMATION PROCESSING APPARATUS - TAKAHASHI MIEKO; SAITO NOBUHIRO; MAEHARA HARUNA; OI NAO; TANABE HIROYASU; TAKAOKA AKI; ISHII TOSHIHIRO; SASAGE HIROSHI (2015)
PROBLEM TO BE SOLVED: To accurately specify the position of information on a screen of a site acquired from the site.SOLUTION: An information processing apparatus 101 searches html data on a screen of a site S for text data having the same content as that of text data, which is obtained from image data on an area T set on image data on the screen of the site S. When a plurality of pieces of text data are searched for, the information processing apparatus 101 changes any one of text data on a plurality of pieces of text data in the html data on the screen of the site S into different text data. The information processing apparatus 101 determines whether or not text data obtained from image data on the area T on image data on the screen of the site S based on the html data on the site S after the change coincides with the changed different text data. The information processing apparatus 101 specifies the text data corresponding to the area T from the plurality of pieces of text data in the html data on the screen of the site S on the basis of a result of the determination. 【課題】サイトの画面情報における、サイトから取得する情報の位置を正確に特定すること。【解決手段】情報処理装置１０１は、サイトＳの画面の画像データ上に設定された領域Ｔの画像データから得られるテキストデータと同一内容のテキストデータを、サイトＳの画面のｈｔｍｌデータから検索する。情報処理装置１０１は、複数のテキストデータが検索された場合、サイトＳの画面のｈｔｍｌデータ内の複数のテキストデータのいずれかのテキストデータを異なるテキストデータに変更する。情報処理装置１０１は、変更後のサイトＳのｈｔｍｌデータに基づくサイトＳの画面の画像データ上の領域Ｔの画像データから得られるテキストデータが、変更した異なるテキストデータと一致するか否かを判定する。情報処理装置１０１は、判定した判定結果に基づいて、サイトＳの画面のｈｔｍｌデータ内の複数のテキストデータから領域Ｔに対応するテキストデータを特定する。【選択図】図１